Upaya Peningkatan Pengetahuan dan Sikap Remaja Tentang Penerimaan Konsep Pendewasaan Usia Perkawinan melalui Pengembangan Model Adolescent Mobile Health - Epti Yorita; Eliana Eliana; Yulinda Yulinda (Universitas Malahayati Lampung, 2022)
ABSTRACT Population is the basic capital and dominant factor of development that must be the central point in sustainable development. Therefore, it is necessary to prevent and control population impacts such as maternal and infant mortality due to pregnancy at a young age, through access to relevant information for adolescents with health promotion regarding Maturation of Marriage Age (PUP). Modification of PIK R based on counseling SMS and SMS remainder through the Adolescent Mobile Health (AdeM Health) program as a model for acceptance of the PUP concept by peer groups is expected to be a leverage for adolescents to increase knowledge and attitudes about PUP. This study aims to determine the effect through the Adolescent Mobile Health (AdeM Health) program on the acceptance of the PUP concept in peer groups in Central Bengkulu Regency in 2019. Research design quasi-experimental pre and post test without a control group. The intervention is in the form of adolescent health promotion through the acceptance model of the PUP concept with the AdeM Health Program in peer groups. The sample of this research is Junior High School Students in Central Bengkulu Regency. The results of the study found that there was an effect of the PUP acceptance model through peer counselors on the knowledge and attitudes of adolescents, there was a PUP acceptance model through the AdeM Health program that was more effective in increasing adolescent knowledge and attitudes than the approach using peer counselors. The development of a model of acceptance of the PUP concept is more effective when using the approach of peer counselors and AdeM Health. Keywords: Adolescents, PUP, AdeM Health, Peer Groups ABSTRAK Penduduk merupakan modal dasar dan faktor dominan pembangunan yang harus menjadi titik sentral dalam pembangunan berkelanjutan. Oleh karena itu perlu dilakukan pencegahan dan pengendalian dampak kependudukan seperti kematian ibu dan bayi akibat hamil usia muda, melalui akses informasi yang relevan pada remaja dengan promosi kesehatan tentang Pendewasaan Usia Perkawinan (PUP). Modifikasi PIK R berbasis sms konseling dan SMS remainder melalui program Adolescnt Mobile Health (AdeM Health) sebagai model penerimaan konsep PUP oleh kelompok sebaya diharapkan mampu menjadi daya ungkit bagi remaja untuk meningkatkan pengetahuan dan sikap tentang PUP. Penelitian ini bertujuan mengetahui pengaruh melalui program Adolescnt Mobile Health (AdeM Health) terhadap penerimaan konsep PUP pada kelompok sebaya Di Kabupaten Bengkulu Tengah Tahun 2019. Desain penelitian quasi eksperimen pre dan post test tanpa kelompok kontrol. Intervensi berupa promosi kesehatan remaja melalui Model penerimaan konsep PUP dengan Program AdeM Health pada kelompok sebaya. Sampel penelitian ini adalah Remaja Siswa SMP di Kabupaten Bengkulu Tengah. Hasil penelitian menemukan ada pengaruh model penerimaan PUP melalui konselor sebaya terhadap pengetahuan dan sikap remaja, ada model penerimaan PUP melalui program AdeM Health lebih efektif untuk meningkatkan pengetahuan dan sikap remaja dibandingkan pendekatan menggunakan konselor sebaya. Pengembangan model penerimaan konsep PUP lebih efektif jika menggunakan pendekatan konselor sebaya dan AdeM Health. Kata Kunci: Remaja, PUP, AdeM Health, Kelompok Sebaya